Analysis of Friction Dynamics of Double Involute Gear Transmission - Wang Mingkai; Fan Zhimin (Jixie chuandong)
In order to study the coupling effect between tribology and dynamics of double involute gear transmission， according to the gear dynamics， load-sharing， and elastohydrodynamic lubrication theory， the friction dynamics model of double involute gears is established， the coupling effect between elastohydrodynamic characteristics and dynamics is studied. The dynamic load solved by the dynamics model is applied to the mixed elastohydrodynamic lubrication model to solve the friction coefficient and other parameters. The friction coefficient is put back into the dynamics model to study the dynamics behavior of double involute gear. The results show that the coupling effect of dynamics and elastohydrodynamic lubrication has a significant effect on the gear dynamics behavior. At low rotating speed， the distribution of friction coefficient and oil film thickness under dynamic load is similar with that under steady load， whereas those distribution changing obviously when the rotational speed increases.